Australia: from Montreal 1976 to Sydney 2000. History of change of model. - Pyke, F.; Noris, K. (2nd International Forum on Elite Sport. Barcelona, Centre d'Alt Rendiment (C.A.R.) de Catalunya, 11-13 September 2001, 2001)
Development of Sports Institutes and Academies The Australian Olympic medal tally between 1980 and 2000 Factors Contributing to Resurgence 1. Institute/Academy Network 2. Adequate Funding 3. Targeted support 4. Programme decentralization 5. Coaching Expertise 6. Utilisation of Support Services 7. Co-operative Relationships Research and development